Effects of Lactobacillus buchneri as a silage inoculant or probiotic on in vitro organic matter digestibility, gas production and volatile fatty acids of low dry-matter whole-crop maize silage - Rabelo, C. H.S. [UNESP]; Basso, F. C. [UNESP]; Lara, E. C. [UNESP]; Jorge, L. G.O. [UNESP]; Härter, C. J. [UNESP]; Mari, L. J.; Reis, R. A. [UNESP] (Wiley, 2017)
Our objective was to investigate Lactobacillus buchneri as a silage inoculant or probiotic on in vitro ruminal measurements of low dry-matter whole-crop maize silage. In vitro gas production was conducted using untreated (without inoculant) and inoculated (treated with L. buchneri CNCM I-4323 at 1 × 105 cfu g−1 of fresh forage) maize silages (wet-ground) incubated with three different ruminal inocula, in a 2 × 3 factorial arrangement. Ruminal fluids were collected from wethers consuming (i) untreated maize silage (RF-U); (ii) inoculated maize silage (RF-I); and (iii) untreated maize silage with a daily dose of L. buchneri CNCM I-4323 administered directly into the rumen (1 × 107 cfu g−1 of supplied silage [LB-probiotic]). Gas production was consistently higher when inoculated silage was used as the substrate of fermentation, compared to the untreated silage. When untreated silage was used as substrate, the total volatile fatty acid concentration was higher using RF-I and LB-probiotic inocula, compared to the RF-U inoculum, at 9 hr and at 48 hr of fermentation. It is concluded that L. buchneri should be used as a silage inoculant rather than as a probiotic because it alters fermentation within the silo thereby improving silage quality and enabling some benefits for ruminal fermentation.
Keywords: lactic acid bacteria; low dry matter; methane; silage quality; volatile fatty acid; whole-crop corn silage